Internalisasi Nilai-Nilai Pancasila dalam Penguatan Kepribadian Mahasiswa Teknik Elektro Politeknik Negeri Malang - Sri Hudiarini (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
Pancasila education is a way to instill a moral and broad minded person. Based on the laws and regulations, namely Law No. 12 of 2012 concerning the implementation of The purpose of research on Pancasila Education discussed at Malang State Polytechnic is to provide students with an understanding that Pancasila is an ideology, the basis of the state and the philosophy / values of the nation with all its implications. It is hoped that it will shape the ethics, behavior and mental attitude of students who are able to appreciate the values of divinity, trust, love for the air and nation, and strengthen civil society that supports, is just and dignified based on Pancasila. And for the achievement of these objectives, it takes a method or strategy in delivering material for students. It is hoped that with appropriate and interesting methods, the learning process of this course will be more easily accepted, understood and understood by students. Keywords: Internalization, Pancasila Values, Students.